Effects of Doppler spread on adaptive orthogonal frequency division multiplexing channel capacity employing diversity in multipath environments. Issue 17 (14th October 2011) - Le, Khoa N.; Dabke, Kishor P.
ABSTRACT: This paper derives the capacity of a fading channel with orthogonal frequency division multiplexing transmission employing diversity techniques and adaptive policies in Rayleigh fading environments. The effects of Doppler shift f d on channel capacity are analysed. The main contribution of this work is to model intercarrier interference as a function of f d and symbol duration T s . Two diversity techniques are considered (i) maximal ratio combining (MRC) and (ii) selective combining (SC). Three adaptive policies are combined with MRC and SC to estimate the following channel capacity: (i) optimal rate adaptive; (ii) optimal power and rate adaptive; and (iii) channel inversion with fixed rate adaptive. Closed‐form expressions and bounds on channel capacity employing different diversity techniques are derived. Simulation results are given. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : This paper studies the impact of Doppler spread on average adaptive channel capacity of orthogonal frequency division multiplexing systems employing maximal ratio combining and selection combining in fading environments. Closed‐form capacity expressions are derived incorporating maximal ratio combining, selective combining and the three following adaptive policies (i) channel inversion with fixed rate; (ii) optimal rate; and (iii) optimal power and rate.